The end of Orson Eerie? - Chabert, Jack (Chabert, Jack. Eerie Elementary, 2019)
Eerie Elementary is planning a big Halloween-type celebration for Eerie Day, including hosting a "haunted house" at the school itself; but the spirit of the evil scientist Orson Eerie sees this as the chance to finally triumph over the intrepid hall monitors, Sam, Lucy, and Antonio--and it is up to them to prevent a catastrophe and perhaps even defeat Orson and banish him from the school forever.